Development of Android-based Augmented Reality Spplications as a Food Promotion Medium - Zain Syakir Naufal; Eka Bagas Purdianto; Indra Laksamana Alam Noer (International Journal of Research and Applied Technology (INJURATECH), 2023)
The development of technology at this time is very rapidly developing in the era of the industrial revolution 4.0, therefore we as the next generation of the nation must make the best use of it. Therefore, one of the uses of this technology is by carrying out food promotion activities using augmented reality technology. Augmented reality itself is the technology that is being widely used for object recognition in the multimedia field. Augmented reality is a technology that combines the virtual world with the real world, with it the virtual world displays objects that will be displayed to the real world. The result of this study is to create an application called scan ar only and make it easier for restaurants to promote their food to be promoted on social media. The application of this technology can increase food sales promotional methods that are different from others, namely, by utilizing the ar scan application only users will be directed to scan the food product, and interesting animations and sounds will appear as a promotional method of the food to be sold. The purpose of this study is to develop an augmented reality mobile application as a promotional medium that aims to introduce food to be promoted to customers. augmented reality in the application which will be built using unity3D software is carried out using a different way of presenting information to other media. The method of using the application is by the way the user sees the image in 2D and or 3D by using the application on a smartphone device. These developed applications can provide an interesting informational and moving animation experience for users of these applications.